Food and feeding habits of mangrove shellfish, Telescopium telescopium (Linnaeus, 1758) in Bangladesh - Zaman, M Beniaz; Jahan, M Sarwar (Bangladesh Journal of Zoology, 2015)
Experiments on food and feeding behaviour of Telescopium telescopium was conducted in the Sundarbans and surrounding area during January to December 2008. The stomach contents of 960 individuals were examined, in which 74.79% and 25.21% were found with and without food respectively. Of the 74.79% stomach with food 16.98%, 18.23%, 21.14% and 18.44% were full fed, ¾ fed, ½ fed and ¼ fed respectively. The intensity of feeding in tidal cycle and monthly sampling periods showed a clear trend. The snail fed mainly at low tide and preferred grazing at day time in winter and night in summer in spring tide. They consumed fine particulate mud along with organic detritus from upper intertidal surface sediment using its long extensible snout. In the time of neap tide especially in winter when the muddy habitat of Telescopium telescopium became dry, the animal survived a long time without food. Bangladesh J. Zool. 41(2): 233-239, 2013